2018
DOI: 10.1002/gsj.1310
|View full text |Cite
|
Sign up to set email alerts
|

When are emerging market multinationals more risk taking?

Abstract: Research Summary: This study examines the endogenous conditions under which emerging market multinationals (EMNEs) are more risk taking in entering and competing abroad. We argue that strategic asset‐seeking intent, financial abundance, and inward internationalization enable EMNEs to better manage uncertainty and capture benefits, resulting in greater levels of risk‐taking behaviors in foreign entry mode and global dispersion. We offer a process framework showing that the effects of endogenous forces on risk‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 134 publications
(305 reference statements)
0
40
0
Order By: Relevance
“…As such, our findings clearly reflect the sample of managers from developed markets. Previous research found that emerging market firms take greater risks, especially in their early stage of internationalization to compensate for their competitive weaknesses and reduce the institutional constraints at home (Cuervo‐Cazurra & Ramamurti, ; Guillén & García‐Canal, ; Luo & Bu, ). It is likely that such firms expand more rapidly into physically, culturally, and economically distant countries (Morck, Yeung, & Zhao, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, our findings clearly reflect the sample of managers from developed markets. Previous research found that emerging market firms take greater risks, especially in their early stage of internationalization to compensate for their competitive weaknesses and reduce the institutional constraints at home (Cuervo‐Cazurra & Ramamurti, ; Guillén & García‐Canal, ; Luo & Bu, ). It is likely that such firms expand more rapidly into physically, culturally, and economically distant countries (Morck, Yeung, & Zhao, ).…”
Section: Discussionmentioning
confidence: 99%
“…Managers' risk‐taking propensity varies across individuals and it depends on the positive and negative expectations of outcomes as well as the aspiration level of the decision maker if they accept a risky alternative (Luo & Bu, ; March & Shapira, ). Miller and Friesen () define risk‐taking propensity as the degree to which managers are willing to make large and risky resource commitments that bear a reasonable chance of costly failure.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…The theoretical contribution of the study is to determine the specificity and identical EMNC's risk behavior. Previous globalization experiences help organizations to be more aggressive and risk-taker through a process of acquiring the existing business and attain global expansion which helps organizations to build strong capacity and capability to survive by reducing the completion in the market (Luo & Bu, 2018).…”
Section: Competitive Strengths / Capacitiesmentioning
confidence: 99%
“…It is important to understand which firm-specific forces importantly affect these firms' risk-taking behaviors. For example, Luo and Bu (2018) find that Chinese MNEs with greater levels of "strategic asset-seeking intent, financial abundance, and inward internationalization present significantly higher risk-taking propensity and risk-taking acts, including risky entry modes such as acquisitions and aggressive geographic dispersion." On the other hand, Akbank, one of the largest Turkish banks, has taken many years and painstaking analyses to expand to neighboring countries (Crossan and Apaydin, 2009).…”
Section: Ribs 293mentioning
confidence: 99%